The Relationship Between Knowledge and Attitude of Postpartum Mothers Towards the Incidence of Primary Postpartum Haemorrhage (Hpp) at Bojonegoro Dander Health Centre - Ernawati, Masfuah; Triyawati, Lilik; Latip, Abdul (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Primary Postpartum Haemorrhage (PPH) is bleeding of more than 500 cc that occurs after the baby is born vaginally or more than 1000 cc after vaginal delivery within 24 hours after birth. In Bojonegoro Regency, the most common cause of maternal death in 2019 was postpartum hemorrhage at 30.8% (8 cases). Based on the LB3 KIA report at the Dander Community Health Center, there was an increase in cases of postpartum hemorrhage by 0.86% from 2019 to 2020. The aim of this study was to analyze the relationship between knowledge and attitudes of postpartum mothers on the incidence of Haemorrhage Postpartum Primary at the Dander Bojonegoro Community Health Center. The type of research used is analytical research with a cross sectional approach. The population of this study was all postpartum mothers in April – June 2021 at the Dander Community Health Center, totaling 135 postpartum mothers. The sample for this study was all postpartum mothers in April – June 2021 who met the inclusion criteria at the Dander Bojonegoro Community Health Center, totaling 101 postpartum mothers. Sampling used simple random sampling. Data analysis used inferential analysis with chi-square using SPSS. The results of this study were that the majority of postpartum mothers' knowledge was sufficient, 45 (44.56%), more than the majority of postpartum mothers' attitudes were negative, 59 (58.41%), more than the majority of postpartum mothers had no primary PPH, 95 (94.05% ), there is a significant relationship between knowledge (P=0.019) and attitude (P=0.033) towards the incidence of primary PPH. It is hoped that postpartum mothers will increase their knowledge by listening to education provided by health workers, newspapers and television about the importance of antenatal care to prevent postpartum bleeding.